KNOWLEDGE AND ATTITUDES RELATED TO HIV/AIDS AMONG MEDICAL AND ALLIED HEALTH SCIENCES STUDENTS - Hussain, Mohammad Akhtar; Chauhan, Abhimanyu Singh; Pati, Sanghamitra; Nallala, Settings Srinivas; Mishra, Jayanti (Indian Journal of Community Health, 2011)
Background: India estimates third highest number of HIV infections in the world, with about 2.4 million people currently living with HIV/AIDS. Adequately trained and sensitized healthcare professionals can play a vital role in combating this epidemic. Limited studies have explored knowledge and attitudes of medical students relating to HIV/AIDS, particularly in the eastern part of India. Methods: The present cross sectional study explored knowledge and attitudes of first year MBBS, BDS & BPT students of Kalinga Institute of Medical Sciences (KIMS), Bhubaneswar, Odisha on HIV/AIDS using a self-administered questionnaire. Data thus collected were analyzedand relevant statistics were calculated. Knowledge and attitude scores were determined and analysis of variance (ANOVA) test was used to examine the equality between the groups. Results: All students scored low on the overall knowledge scale (<10/15). Specifically, knowledgewas low on modes of transmission and treatment. Attitudinal scores in the areas of precautions and need for training on HIV was low for all the three streams.The willingness to treat HIV/AIDS patient was found to be high amongst study participants. Conclusion: There is a need and scope to provide correct and detailed information on HIV/AIDS for new entrants in medical and allied health sciences to help them acquire adequate knowledge and develop appropriate attitudes towards HIV/AIDS.